Latvian experience in conservative management of abnormally invasive placenta: two case reports - Bokučava Diana; Vītiņa Sandra; Jansone, Maira; Tirāne Mara; Krastiņa Zane; Prostaka, Kristine; Vedmedovska, Natalija (Acta medica Lituanica, 2020)
Background. Abnormally invasive placentation (AIP) is a clinical term that describes situation when placenta does not separate spontaneously after delivery and its manual removal causes excessive bleeding (1). Historically, the treatment of choice for this condition is hysterectomy. Lately, the new treatment option, conservative management of the AIP, has proven itself an effective alternative to hysterectomy in carefully selected patients (2). However, the use of conservative AIP management is limited in many countries, the reasoning being the lack of doctors’ experience in this procedure and concerns regarding a high postpartum infection rate. Case reports. We present the first two cases of conservative management of AIP in Latvia. Most of prenatally diagnosed AIP cases country-wide are referred to the Paul Stradinš University Hospital, which is a tertiary referral hospital. The annual rate of AIP in the hospital varies from five to ten cases. Two pregnant women were diagnosed with AIP prenatally, both of them refused hysterectomy and therefore went for the conservative management of AIP. During Caesarean section operation, placentas were left in situ after delivery of the baby. During the follow-up period of 12 and 14 weeks, both women developed infection complications, but complete placental tissue resolution was diagnosed in the end. Conclusion. These two cases demonstrate that conservative management of AIP can be safely applied in small countries/areas with small AIP rate and management experience.